Association of adipocyte enhancer‐binding protein 1 with Alzheimer's disease pathology in human hippocampi - Shijo, Masahiro (Brain Pathol, 2017)
Adipocyte enhancer binding protein 1 (AEBP1) activates inflammatory responses via the NF‐κB pathway in macrophages and regulates adipogenesis in preadipocytes. Up‐regulation of AEBP1 in the hippocampi of patients with Alzheimer's disease (AD) has been revealed by microarray analyses of autopsied brains from the Japanese general population (the Hisayama study). In this study, we compared the expression patterns of AEBP1 in normal and AD brains, including in the hippocampus, using immunohistochemistry. The subjects were 24 AD cases and 52 non‐AD cases. Brain specimens were immunostained with antibodies against AEBP1, tau protein, amyloid β protein, NF‐κB, GFAP and Iba‐1. In normal brains, AEBP1 immunoreactivity mainly localized to the perikarya of hippocampal pyramidal neurons, and its expression was elevated in the pyramidal neurons and some astrocytes in AD hippocampi. Although AEBP1 immunoreactivity was almost absent in neurons containing neurofibrillary tangles, AEBP1 was highly expressed in neurons with pretangles and in the tau‐immunopositive, dystrophic neurites of senile plaques. Nuclear localization of NF‐κB was also observed in certain AEBP1‐positive neurons in AD cases. Comparison of AD and non‐AD cases suggested a positive correlation between the expression level of AEBP1 and the degree of amyloid β pathology. These findings imply that AEBP1 protein has a role in the progression of AD pathology.